ASSESSMENT OF NEONATAL OUTCOME OF OPERATIVE VAGINAL DELIVERY AND ITS DETERMINANTS AT DILLA UNIVERSITY REFERRAL HOSPITAL, SOUTH ETHIOPIA - Feyisso Shaka, Mohammed; Lubduno, Aklilu; Kassa Abebe, Reta (Ethiopian Journal of Reproductive Health, 2019)
ABSTRACT INTRODUCTION: Assisting laboring women to deliver vaginally using specialized instruments is a practice that dates back several centuries. Forceps and vacuum are the most popular of the operative vaginal procedures used in medical practice. Both are associated with increased risk of neonatal morbidity when compared to normal spontaneous vaginal delivery. OBJECTIVE: This study was aimed to assess neonatal outcome of operative vaginal delivery and its determinants. METHODS: Hospital based cross sectional retrospective study of women delivered between September 2013 and August 2015 in Dilla University Referral Hospital was conducted. All records of women delivered within the specified period of time was used as a total sample size. Data was entered into SPSS version 20 for analysis. Descriptive, bivariate & multivariate logistic regression was done to assess factors associated with the neonatal outcome. RESULT: Data was collected from 216 women delivered by operative vaginal delivery of which 133 (61.6%) were delivered by vacuum, 76 (35.2%) were delivered by forceps and 7 (3.2%) by sequential use. Significant number of neonates 91(42.1%) delivered by operative vaginal delivery ended up with poor APGAR score. Birth weight of the neonate [AOR: 3.0 8, (CI: 1.16 , 8.20 )] and ind ication for operative vaginal d elivery [AOR: 2.56 (CI: 1.22, 5.38)] were found to increase the risk of poor neonatal outcome. CONCLUSIONS: Neonatal outcome with respect to APGAR score was significantly poor among operative vaginal deliveries in this study. Neonates with lower birth weight and operation done with the indication of fetal distress resulted in higher risk of poor outcome. KEYWORDS: APGAR Score; Operative vaginal delivery; Dilla University Referral Hospital